Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


F(x) = 3x-1
Let y  = 3x-1
step 1,  interchange  x & y
 x = 3y -1
step 2,  solve for y in term of x
3y = x+1
y =( x + 1)/3
thus the inverse
 f⁻¹(x) =  (x+1)/3
note not every function have an inverse,only one to one function

0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts